- TINJAUAN YURIDIS TINDAK PIDANA MEMPERTONTONKAN DIRI DI MUKA UMUM YANG MENGGAMBARKAN KETELANJANGAN/EKSHIBISIONISME: TINDAK PIDANA MEMPERTONTONKAN DIRI DI MUKA UMUM YANG MENGGAMBARKAN KETELANJANGAN/EKSHIBISIONISME - Oemyx Wynn Tratabofa Hutasoit; Ermania Widjajanti (Faculty of Law, Universitas Trisakti, 2024)
Criminal perpetrators exposing their genitals fall under the purview of both the Criminal Code and Law Number 44 of 2008 regarding Pornography. However, the defendant's actions, primarily targeting children, align more with Law 35 of 2014 concerning Amendments to Child Protection Law Number 23 of 2002. The defendant's exhibitionism, particularly in front of children, raises questions about the judge's classification of the crime. The research, utilizing normative methods and various data sources, explores this issue. The judge sentenced the defendant to 2 years in prison under Article 36 of the Pornography Law, but the author argues this ruling fails to consider most victims being children. Consequently, the author suggests that the perpetrator's sentence should be assessed under the Child Protection Law, potentially warranting aggravated or recalculated penalties.